Crossroads arts district: a case study of cultural district development - McKennan, Victoria Adams (Kansas State University, 2011)
Community leaders have substantial interest in fostering the local cultural economy as the arts attract both businesses and residents. Because art and creativity are regarded as spontaneous, organic processes, most researchers recommend planning initiatives that capitalize on a community’s existing cultural economy rather than producing contrived elements of creativity. One strategy that fits the framework of such recommendations is the concept of cultural district development. These districts typically evolve naturally to some extent, due to pre-existing urban form and cultural activities. Because this revitalization strategy does not demand large public investments, it is attractive to public leaders. However, revitalization strategies may have unanticipated results at the detriment to those “urban pioneers” who initially improved the area and catalyzed the districts’ reinvestment. While such districts rely on the collaborative efforts of community members, local governments and public organizations can play a pivotal role in allowing them to address such threats with effective policies. This master’s report investigates the process and effects of cultural district development through a case study of the Crossroads Arts District in downtown Kansas City, Missouri. This illustrates how this particular district evolved, why and how planning initiatives formalized the district, what processes and players were involved, and the resulting changes to the area. As the Crossroads Arts District is becoming increasingly formalized, this report will explore the past, present, and future of the neighborhood with insights drawn from interviews and supplementary historical document review. Through a case study of planning activities, through the scope of cultural district development, this report illustrates the organic nature of creative synergy, the importance of community associations, the relationship between the arts and revitalization, the role of public planning in addressing citizen needs, and the dynamic character of communities.
Keywords: Cultural district development; cultural capital; Urban regeneration; Tax abatement; Artist retention; Urban Planning (0999)